Editing Leibniz in Turin. Convegno internazionale dedicato a Louis Dutens in occasione del 250° della pubblicazione dell’Opera Omnia di G. W. Leibniz - Roberto Palaia (Lexicon Philosophicum)
The note provides a report on the International Conference Editing Leibniz in Turin. Louis Dutens’ 1768 Grand Edition 250 Years After, which has been hold in Turin in December 2018. In the report are briefly illustrated the papers and the results of the discussion.